Differentiated instruction strategies to improve mathematics learning outcomes in elementary school - Oktavia, Windi; Asmara, Andes Safarandes; Suparman, Tarpan (Universitas Papua, 2025)
Mathematics learning in elementary schools often faces persistent challenges arising from the heterogeneity of students’ abilities and learning needs, which frequently hinder the achievement of optimal learning outcomes. Although differentiated instruction has been widely recognized as a promising pedagogical approach for addressing learner diversity, empirical evidence on its effectiveness in mathematics education at the elementary level particularly within the Indonesian context remains limited. This study contributes to filling this gap by examining the impact of differentiated instruction on the mathematics learning outcomes of elementary school students. Employing a quantitative approach with a pre-experimental one-group pretest–posttest design, the study involved 43 purposively selected fifth-grade students from SDN Belendung III during the 2023/2024 academic year. Data were collected through pretest and posttest essay assessments consisting of 10 items and analyzed using SPSS version 24 with a paired sample t-test. The analysis revealed a significant improvement in students’ learning outcomes, with a calculated t-value of 42.187 exceeding the critical value of 2.02, thereby confirming the positive effect of differentiated instruction. These findings highlight the potential of adaptive teaching practices to enhance students’ conceptual understanding and problem-solving skills in mathematics. The study underscores the importance of implementing evidence-based differentiation strategies to promote more inclusive and effective mathematics instruction. The results also provide a foundation for future research to investigate the long-term sustainability of differentiated instruction, its role in shaping students’ attitudes toward mathematics, and the comparative efficacy of specific differentiation techniques.